2017
DOI: 10.7755/fb.115.3.4
|View full text |Cite
|
Sign up to set email alerts
|

Investigations into the distribution of sample sizes for determining age composition of multiple species

Abstract: Abstract-Collecting age-composition data is a critical aspect of stock assessment; however, there are no biological or statistical investigations that support optimization of the distribution of sample size across species. Sample sizes for both collection and age-reading are often set by using ad hoc or historical values. Investigations into quantifying the trade-offs when allocating sample sizes across species are needed because resources for age determination are always limited. In this study we performed an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
4
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 5 publications
1
4
1
Order By: Relevance
“…() and Walleye Pollock Gadus chalcogrammus in Hulson et al. () did not have as large a recruitment SD as those of Bocaccio in He et al. () or Cisco in our study (σ r ; sardine = 0.73, Walleye Pollock = 0.70, Boccacio = 1, Cisco full model estimate = 4.5).…”
Section: Discussioncontrasting
confidence: 47%
See 2 more Smart Citations
“…() and Walleye Pollock Gadus chalcogrammus in Hulson et al. () did not have as large a recruitment SD as those of Bocaccio in He et al. () or Cisco in our study (σ r ; sardine = 0.73, Walleye Pollock = 0.70, Boccacio = 1, Cisco full model estimate = 4.5).…”
Section: Discussioncontrasting
confidence: 47%
“…Although as a counter example, Hulson et al. () found that age composition sample size had a greater impact on SCAA uncertainty for species with higher recruitment variability compared with those with lower recruitment variability. In addition, Ono et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…When ages are determined from scales, biases are not expected; however, when ages are determined from length, biases can exist [20]. The sample size used to derive age-length frequency has an influence on the accuracy of the age-length relationship [27,28]; the uncertainty in age structure owing to age-length data needs to be considered.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, multi-stage design is very common in the monitoring of fish populations, whereby fish are caught at different sampling sites, all or a high proportion of the fish in that catch are measured for length, but only a sub-sample of the measured fish are aged. Comparisons of different sub-sampling designs for collecting and studying the distribution of a particular trait, such as age composition of a populations (Kimura, 1977; Pennington, Burmeister & Hjellvik, 2002; Chih, 2009; Hulson, Hanselman & Shotwell, 2016), have been more thoroughly studied in fisheries science than in other ecology fields (Kosmelj, Cedilnik & Kalan, 2001; Stafford et al, 2006; Smith et al, 2011; Brown et al, 2013). Thus, the sampling design to gather data on population abundance (stage 1) is paramount in ecological research, but also the sub-sampling design to gather data on traits-structure in the population (stage 2 or 3) can have a major impact on the population estimates, which will be used as reference points for assessment and management.…”
Section: Introductionmentioning
confidence: 99%